HONEYBEES’ BEHAVIOUR IN A FARADAY-SHIELDED HIVE : MANDATORY SCHUMANN RESONANCE FOR COLONY SURVIVAL - Favre, Daniel; Johansson, Olle (International Journal of Research -GRANTHAALAYAH, 2025)
Research shows that low-level anthropogenic electromagnetic fields negatively impact various species in their behaviour, affecting orientation, migration, foraging, reproduction, nesting, territorial defense, vitality, and survival. Many insects, like honeybees, rely on Earth’s electromagnetic fields for orientation and foraging. The honeybees react negatively to anthropogenic multi-frequency interference through multi-sensory mechanisms. In order to circumvent the potentially negative effects of external electromagnetic influence, the honeybees were kept in Faraday hives. Placing honeybees in such Faraday-shielded cages, which block external electromagnetic fields, effectively isolates them from natural electromagnetic frequencies. However, the long-term survival of the honeybees in such Faraday hives was only possible with the artificial re-introduction of the Earth’s natural electromagnetic environment, the Schumann resonance. Honeybees placed in Faraday cages without access to the Schumann resonance experience a range of effects, including physiological impairments to the queen of the honeybees’ colony, which stops laying fertilized eggs. This is leading to the collapse of the colony, which is finally containing only immature female workers and drones. These findings highlight the significance of natural electromagnetic fields in maintaining homeostasis and normal biological functions of honeybees. Further research is needed to explore factors like electromagnetic radiation affecting honeybee physiology and behaviour. The combined effect of multiple stressors, interacting across space and time, likely plays a central role in the global decline of honeybee health.